Penerapan E-Book sebagai Media Pembelajaran untuk Meningkatkan Pemahaman Struktur Kalimat: Studi Kasus di Kelas IV SD Negeri 12 Langsa - Escanna Kabeakan; Melianda Futri; Delima Putri; Eva Sakinah; Juliati Juliati (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
One of the important competencies that elementary school students must have in learning Indonesian is understanding sentence structure. However, conventional learning approaches are often uninteresting and do not meet students' learning needs. The purpose of this study was to determine how effective books are as a learning tool in improving students' understanding of sentence structure in grade IV of SD Negeri 12 Langsa. This study used qualitative descriptive methodology and case studies. After the e-book was displayed during the learning process, the researcher gave students a questionnaire to find out their responses and their level of understanding of the material. Data were collected through observation, interviews, and questionnaires with teachers. The study showed that the use of e-books increased students' attention, understanding, and interest in learning. Students can understand sentence structure more clearly and enjoyably thanks to the visual display and interactive features of the e-book. The results show that e-books can be an effective tool for teaching. In addition, these findings encourage teachers to use technology in teaching Indonesian in elementary schools.